Pembelajaran Komunikasi Data Berbasis Simulasi Virtual - Zulkipli, Zulkipli; Rania, Salwa; Purnomo, Reno; Syahrian, Ekal (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to evaluate the implementation and effectiveness of virtual simulation-based data communication learning. Using a quasi-experimental method with a one-group pre-test and post-test design, this study involved students taking the Data Communication course. This innovative learning was implemented for one full semester. Data were collected through pre-test and post-test to measure students' understanding and skills, as well as questionnaires to obtain students' perceptions of learning. Data analysis was done quantitatively using paired sample t-test to compare pre-test and post-test scores, and descriptive percentage analysis to evaluate questionnaire responses. The results show that virtual simulation-based data communication learning is significantly able to improve learning effectiveness, as well as student understanding and skills. Therefore, virtual simulation-based learning is highly recommended as an effective alternative learning approach in the field of information technology.